Comparison of Five Methods for the Determination of Rubella Immunity - Robert L. Sautter; Arthur E. Crist; Lynn M. Johnson; William D. LeBar (Hindawi Limited, 1994)
Objective: The purpose of this study was to compare the accuracy of commonly used methods for the detection of rubella immunity, especially the fully automated IMx assay.